LHX3 deficiency presenting in the United States with severe developmental delay in a child of Syrian refugee parents - Ahern, Susan (Endocrinol Diabetes Metab Case Rep, 2018)
In this case report, we present a novel mutation in Lim-homeodomain (LIM-HD) transcription factor, LHX3, manifesting as combined pituitary hormone deficiency (CPHD). This female patient was originally diagnosed in Egypt during infancy with Diamond Blackfan Anemia (DBA) requiring several blood transfusions. Around 10 months of age, she was diagnosed and treated for central hypothyroidism. It was not until she came to the United States around two-and-a-half years of age that she was diagnosed and treated for growth hormone deficiency. Her response to growth hormone replacement on linear growth and muscle tone were impressive. She still suffers from severe global development delay likely due to delay in treatment of congenital central hypothyroidism followed by poor access to reliable thyroid medications. Her diagnosis of DBA was not confirmed after genetic testing in the United States and her hemoglobin normalized with hormone replacement therapies. We will review the patient’s clinical course as well as a review of LHX3 mutations and the associated phenotype. LEARNING POINTS: Describe an unusual presentation of undertreated pituitary hormone deficiencies in early life. Combined pituitary hormone deficiency due to a novel mutation in pituitary transcription factor, LHX3. Describe the clinical phenotype of combined pituitary hormone deficiency due to LHX3 mutations.